Edukasi Pemanfaatan Daun Kelor dengan Media Audio Visual terhadap Mean Arterial Preasure pada Penderita Hipertensi - I'maliya, Dewi; Sukesih Sukesih; Soesanto, Edi (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypertension is a major public health problem that significantly contributes to morbidity and mortality due to cardiovascular diseases. Effective hypertension management requires not only pharmacological therapy but also non-pharmacological approaches supported by appropriate health education. This study aimed to analyze the effect of Moringa oleifera leaf decoction combined with audio-visual health education on the reduction of Mean Arterial Pressure (MAP) among patients with hypertension. This study employed a quasi-experimental design with a control group pre-test and post-test approach. A total of 32 respondents were selected using purposive sampling and divided into an intervention group and a control group, each consisting of 16 participants. The intervention group received health education on the utilization of Moringa oleifera leaves through audio-visual media and consumed Moringa oleifera leaf decoction for seven consecutive days, while the control group received health education without the herbal intervention. MAP measurements were conducted before and after the intervention. Data were analyzed using the Paired Sample T-Test and Independent Sample T-Test. The results showed a significant decrease in MAP in the intervention group compared to the control group, with a p-value of 0.001 (p < 0.05). These findings indicate that the administration of Moringa oleifera leaf decoction combined with audio-visual-based health education is effective in reducing Mean Arterial Pressure among patients with hypertension. This intervention may serve as a supportive non-pharmacological strategy for hypertension management in primary healthcare settings.